2020
DOI: 10.1016/j.ijid.2019.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Preventive tuberculosis treatment effect on QuantiFERON TB-Gold in-tube testing in a high tuberculosis-endemic country: A clinical trial

Abstract: Background: Whether T-cell interferon-g responses to Mycobacterium tuberculosis-specific antigens can be influenced by tuberculosis preventive treatment in a high-endemic country is uncertain. Methods: In this prospective, open-label, controlled study, 513 individuals with silicosis were randomly selected for TB preventive treatment with rifapentine and isoniazid or for observation. QuantiFERON-TB Gold in-tube (QFT-GIT) assay was used to measure IFN-g response to M. tuberculosis antigens at baseline (T0) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…So far, WHO has endorsed three IGRA tests, T-SPOT 1 .TB (Oxford Immunotec, Abingdon, UK), Beijing Wantai's TBIGRA (Wantai), and QuantiFERON 1 -TB Gold Plus (QFT, QIAGEN, Hilden, Germany), able to measure IFN-γ released by both CD4 and CD8 T cells [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…So far, WHO has endorsed three IGRA tests, T-SPOT 1 .TB (Oxford Immunotec, Abingdon, UK), Beijing Wantai's TBIGRA (Wantai), and QuantiFERON 1 -TB Gold Plus (QFT, QIAGEN, Hilden, Germany), able to measure IFN-γ released by both CD4 and CD8 T cells [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…After controlling the probable confounders involving baseline TB-IGRA, the pretreatment prophylactic therapy did not influence the elevating TB-IGRA value, and there was no significant increase in the ATB or NTB group. We considered that the increasing tendency of TB-IGRA values in the current study might be correlated with the high epidemic background rather than receiving prophylactic treatment based on previous evidence [ 22 ]. Furthermore, combining the results of the TB status mentioned, we found that none of the patients developed active TB despite varying TB-IGRA values.…”
Section: Discussionmentioning
confidence: 99%
“…However, IGRA does not measure the infection itself; it is a surrogate immunological test which cannot distinguish between active TB and LTBI. Notably, preventive TB treatment has no effect on the results of a QuantiFERON-TB Gold In-Tube (QFT-GIT) assay, a type of IGRA, when evaluated in a highly TB-endemic country ( 10 ).…”
Section: Introductionmentioning
confidence: 99%